Eu conto, tu contas... histórias para quem tem história: contribuições para a aprendizagem na EJA - Pinto, Maria Lídia de Moraes (2012)
The research Eu conto, tu contas Histórias para quem tem história has been developed with students and teachers of Youth and Adults. Qualitative in nature, the survey sought to determine the contributions which the art of storytelling to the process of teaching and learning of this type of education. For this purpose, references in writers sought related to both practice and theory of teaching as the art of storytelling: Shulman, Mizukami, Freire, Fromm, Haddad, di Piero, Bettelheim, Bosi, Machado, among others. Was also carried out an intervention with stories that range from the very act of them has, through format issues related to their teaching and life. This process occurred through meetings with two groups of adult education. The methodology used for the analysis was to study the material record made in photos, DVD, writing and direct observation of meetings. In the results, we attempted to observe aspects of the relations existing between the group members, especially teachers and students, and also its relations with concepts and ideas that permeate the acts of teaching and learning.